2009
DOI: 10.1096/fj.09-130260
|View full text |Cite
|
Sign up to set email alerts
|

Development of microfluidics as endothelial progenitor cell capture technology for cardiovascular tissue engineering and diagnostic medicine

Abstract: We have developed a unique microfluidic platform capable of capturing circulating endothelial progenitor cells (EPCs) by understanding surface chemistries and adhesion profiles. The surface of a variable-shear-stress microfluidic device was conjugated with 6 different antibodies [anti-CD34, -CD31, -vascular endothelial growth factor receptor-2 (VEGFR-2), -CD146, -CD45, and -von Willebrand factor (vWF)] designed to match the surface antigens on ovine peripheral blood-derived EPCs. Microfluidic analysis showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 28 publications
1
70
0
2
Order By: Relevance
“…43 Other cardiovascular targets for EPCs include coating of ventricular assist devices and artificial hearts. 44,45 Together, these studies indicate that a number of progenitor cell types exist, with translational potential in therapies as diverse as vasculogenesis augmentation, tissue engineering, hybrid graft/device functionalization, plaque stabilization, modulation of vascular remodeling in pulmonary hypertension, and transplant atherosclerosis prevention. Emerging clinical applications of vascular progenitor cells are illustrated in Figure 2.…”
Section: Kumar and Caplice Potential Of Adult Vascular Progenitor Celmentioning
confidence: 99%
“…43 Other cardiovascular targets for EPCs include coating of ventricular assist devices and artificial hearts. 44,45 Together, these studies indicate that a number of progenitor cell types exist, with translational potential in therapies as diverse as vasculogenesis augmentation, tissue engineering, hybrid graft/device functionalization, plaque stabilization, modulation of vascular remodeling in pulmonary hypertension, and transplant atherosclerosis prevention. Emerging clinical applications of vascular progenitor cells are illustrated in Figure 2.…”
Section: Kumar and Caplice Potential Of Adult Vascular Progenitor Celmentioning
confidence: 99%
“…Previous reports (1)(2)(3)(4), for example, have shown that the concentration of circulating tumor cells (CTCs) within a cancer patient's blood can act as a therapeutic monitoring tool (1)(2)(3)(4). Additionally, the isolation of adult stem cells provides a needed cell source for tissue engineering and regenerative medicine treatments (5,6). Finally, separation and genomic analysis of key cell populations from patients allows for targeted treatment regimens (7,8).…”
mentioning
confidence: 99%
“…After binding, antibody mediated adhesion was not disrupted, even if the shear rate was increased to arterial shear rate. Furthermore, Plouffe et al conjugated the surface of a microfluidic device with antibodies against CD34 or VEGFR-2 to capture in vitro cultivated ovine peripheral blood-derived EPCs (Plouffe et al, 2009). …”
Section: Vegfr-2 Mabmentioning
confidence: 99%